The language characteristics and learning strategies of Allied Medical Students - Lacson, Maria Carisa R.
This study focused on describing the relationship between the language characteristics and learning strategies of allied medical students. This research aimed to: (a) describe the language characteristics of the allied medical students in terms of use and comfort level; (b) describe the students? current learning strategies; and (c) determine the relationship between language characteristics and learning strategies. The independent variables were the language characteristics and the dependent variables were the learning strategies. Research design was descriptive in nature and it was a survey design. Focus group discussions, expert validation, and pilot testing were conducted prior to the implementation of the study. Then, a survey among the third year allied medical students took place. The survey questionnaire was a tool that was developed, constructed and implemented for this study. Data was analyzed using descriptive statistics. After which, data was presented using tabular and graphical presentations. Findings revealed that in terms of language characteristics, the study population mostly used English and Filipino to communicate. English was used in most settings except for the home. Straight English was used and was comfortable during non-speaking tasks. Majority of the respondents were English thinkers with a high comfort level. With regard to learning strategies, the students preferred to study at their residence 2-3 days before a test for more than 4 hours a day. Learning was best after reading the text, notes, or book. Learning strategies used were behavioral in nature: highlighting, making reviewers, and reading, watching videos, listening to recordings several times. Generally, there were no significant relationships between the language characteristics (English translators with a high comfort level, English translators with a low comfort level, English thinkers with a low comfort level) and the learning strategies used per given task. This means that the choice of learning strategy does not depend on the language characteristics a person has.